2017
DOI: 10.1200/jco.2017.35.4_suppl.113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tumor response and treatment schedule on the distribution of tumor recurrence in esophageal cancer patients treated with neoadjuvant chemoradiotherapy.

Abstract: 113 Background: Knowledge of pathologic complete tumor response (pCR) and the used neoadjuvant chemoradiotherapy (nCRT) schedule on the distribution of recurrent disease is important in the treatment of esophageal cancer (EC) patients. We assessed the effect of both pCR and different nCRT schedules on the pattern of first tumor recurrences in EC. Methods: The study was performed in two different centers in patients with T1N+/T2-4aN0-3/M0 EC. Patients were treated with nCRT according to the CROSS (carboplatin/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…1,11 Despite these outcomes, other studies have reported that 21% to 39% of patients with a pCR still have recurrence. [8][9][10] In our study, 61 patients with pCR experienced recurrence of disease. To date, few studies have assessed whether clinical and pathologic characteristics may predict recurrence in this patient population.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…1,11 Despite these outcomes, other studies have reported that 21% to 39% of patients with a pCR still have recurrence. [8][9][10] In our study, 61 patients with pCR experienced recurrence of disease. To date, few studies have assessed whether clinical and pathologic characteristics may predict recurrence in this patient population.…”
Section: Discussionmentioning
confidence: 59%
“…1,6 The degree of response to chemoradiotherapy is a strong predictor of both OS and DFS, and several studies have demonstrated that patients with a pCR have better OS and DFS and lower rates of recurrence in comparison with patients with residual disease contained in the surgical specimen despite complete resection. [7][8][9] In particular, for patients with pCR, 5-year OS and DFS have been reported to be approximately 50% regardless of histology. [10][11][12][13] Despite these positive results, 21% to 39% of patients who achieve pCR do have recurrence, predominantly within 2 years post-treatment.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…However, recurrence rate after pCR remains an issue. Although the recurrence rate is quite low compared to that of non-pCR patients, 28 >20% of patients still relapse after trimodal treatment 29,30 . We experienced a recurrence rate of 13.9%.…”
Section: Discussionmentioning
confidence: 70%
“…Despite the improvement in multimodal treatment during the past several years, the prognosis of esophageal cancer remains poor [2][3][4][5][21][22][23][24]. One of the main reasons is the high frequency of tumor recurrence following curative-intended surgery [5,25].…”
Section: Discussionmentioning
confidence: 99%